2020
DOI: 10.1002/slct.202002787
|View full text |Cite
|
Sign up to set email alerts
|

Nickel‐Catalyzed Carbon‐Sulfur Bond Formation through Couplings of Aryl Iodides and Aryl Ethanethioates

Abstract: A nickel‐catalyzed reductive coupling between aryl iodides and aryl ethanethioates has been developed to afford diaryl sulfides. This method provides a novel and practical route to aryl thioetherification and can be effectively applied to electronically diverse aryl iodides without expensive metals such as palladium and ruthenium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Unfortunately, this one-pot protocol for the formation of S-thioesters was unsuccessful with S-aryl ethanethioates as substrates as used in our previous work. 20…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, this one-pot protocol for the formation of S-thioesters was unsuccessful with S-aryl ethanethioates as substrates as used in our previous work. 20…”
Section: Discussionmentioning
confidence: 99%
“…In the same year, Wu et al also reported a thiocarbonylation of arylboronic acids with sulfonyl chlorides for the synthesis of thioesters by nickel catalyst (Scheme 1c) [13c] . Inspired by these works, herein we disclose a three‐component nickel‐catalyzed carbonylation reaction of aryl iodides with disulfides under CO‐gas‐free conditions to produce the thioesters as our continued studies on nickel‐catalyzed C−S bond formation or cleavage [14a–b] . (Scheme 1d).…”
Section: Introductionmentioning
confidence: 85%
“…720 Aryl iodides with electron-donating substituents produce high yields in the reaction with arylthioacetates catalyzed by Ni(II)/bpy in the presence of Zn (Scheme 206, A). 721 Aryl iodides with p-NO 2 or p-CN groups do not react.…”
Section: Other Metals In C−z Cross-coupling Reactionsmentioning
confidence: 99%